Molecular detection of HHV1-5, AAV and HPV in semen specimens and their impact on male fertility. (3rd April 2019) - Behboudi, Emad; Mokhtari-Azad, Talat; Yavarian, Jila; Ghavami, Nastaran; Seyed Khorrami, Seyed Mahmood; Rezaei, Farhad; Charostad, Javad; Shatizadeh Malekshahi, Somayeh; Shafiei-Jandaghi, Nazanin Zahra
Abstract: Viral infections have been considered as possible destructive factors that influence male fertility. The aim of this study was to determine the prevalence of human herpes viruses 1-5 (HHV1-5), adeno associated virus (AAV) and human papilloma virus (HPV) in semen and whether these influence semen quality. DNA extraction was performed using phenol–chloroform protocol, then three different nested-PCRs were done to detect HHV1-5, AAV and HPV DNAs in the semen samples. Of 145 samples, 66 (45.5%) were positive at least for one of the viruses. The genome detection rate of HSV1/2, VZV, EBV, HCMV, AAV and HPV were zero, 2.8%, zero, 1.4%, 27.6% and 19.3%, respectively. Of 66 positive samples for these viruses, 6 (4.1% of all samples) were positive for two viruses simultaneously. Here no association was found between variations in semen parameters related to fertility and detection of VZV, HCMV, AAV and HPV DNA in semen samples. It should be noted that the prevalence of different viruses in semen, and their relevance to male infertility, differs significantly due to the genome extraction and amplification methods or due to a real variation between study populations and geographical regions.